Concentration Kinetics of Secoisolariciresinol Diglucoside and its Biosynthetic Precursor Coniferin in Developing Flaxseed. Issue 1 (12th June 2012) - Fang, Jingjing; Ramsay, Aina; Paetz, Christian; Tatsis, Evangelos C.; Renouard, Sullivan; Hano, Christophe; Grand, Eric; Fliniaux, Ophélie; Roscher, Albrecht; Mesnard, Francois; Schneider, Bernd
ABSTRACT Introduction In the plant kingdom, flaxseed (Linum usitatissimum L.) is the richest source of secoisolariciresinol diglucoside (SDG), which is of great interest because of its potential health benefits for human beings. The information about the kinetics of SDG formation during flaxseed development is rare and incomplete. Objective In this study, a reversed‐phase high‐performance liquid chromatography–diode array detection (HPLC‐DAD) method was developed to quantify SDG and coniferin, a key biosynthetic precursor of SDG in flaxseed. Methodology Seeds from different developmental stages, which were scaled by days after flowering (DAF), were harvested. After alkaline hydrolysis, the validated HPLC method was applied to determine SDG and coniferin concentrations of flaxseed from different developing stages. Results Coniferin was found in the entire capsule as soon as flowering started and became undetectable 20 DAF. SDG was detected 6 DAF, and the concentration increased until maturity. On the other hand, the SDG amount in a single flaxseed approached the maximum around 25 DAF, before desiccation started. Concentration increase between 25 DAF and 35 DAF can be attributed to corresponding seed weight decrease. Conclusion The biosynthesis of coniferin is not synchronous with that of SDG. Hence, the concentrations of SDG and coniferin change during flaxseed development. Copyright © 2012 John Wiley & Sons, Ltd.